The Correlation of Exercise and Range of Motion (ROM) on Elderly Knee Observasional Study on Elderly People in Pedurungan Semarang - Widyantoro, Adhitya Putra; Rosdiana, Ika; Fasitasari, Minidian (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: In aging process, decreasing of musculosceletal capabilities will reduce physical activity and excercise, as well as Range Of Motion (ROM). In order to maintain the normality of ROM, joints and muscles should be moved regularly. However many elderly people are still less physically active, due to lack of knowledge, no free time for physical activity, and lack of support from the social environment. This study aimed to determine the correlation of excercise on ROM of knee in the elderly in Pedurungan District, Semarang.Design and Method: Observastional study with a cross sectional design 80 elderly men and women were divided into 2 groups: gymnastics group in the Social Rehabilitation Unit Of Pucang Gading (n=40) and unexcercises group in the Penggaron village (n=40). In both groups, the degree of ROM of knee was assessed using the Goniometer. To evaluate the value of its significance, the data were analyzed using the Mann Withney test followed by Spearmann’s rho test.Result: ROM for gymnastic(exercised group) and unexercised group were 115.50°±11.591°, 95.38°±12.780° respectively with p<0. 001. Resuts showed that doing exercise was useful for maintaining ROM of knee in elderly people. Spearmann’s rho test resulted in a strong correlation between ROM and exercise with r value of 0.652.Conclusion: exercise correlates with ROM of knee in elderly (Sains Medika, 4(1):39-45).